Sustainability performance indicator trends: A Canadian industry-based analysis - Michel Coulmont; Sylvie Berthelot; Vincent Gagné (International Journal of Corporate Social Responsibility (JCSR), 2022)
This study aims to examine the trends in the sustainability performance indicators disclosed in sustainability reports by Canadian companies. Our sample is comprised of eight companies in four sectors and our observations cover a 19-year period. The results of our analysis show a general increase over time of sustainability performance indicators disclosed, as well as varying degrees of coverage of the three sustainability dimensions. While the focus was more on environmental performance in the early 2000s, social performance indicators, such as employment practices and human rights, have now gained more traction. In addition, the scope of sustainability performance indicators disclosed in sustainability reports reached a plateau around 2010. Our results highlight the need for a standardised approach to sustainability reporting that would help overcome the shortcomings of voluntary initiatives and improve the overall comparability of voluntary reporting mechanisms.
Keywords: 650; Comparability; Corporate social responsibility; Sustainability reporting; Sustainable performance indicators; Voluntary disclosure